Histone Deacetylase HDA9 With ABI4 Contributes to Abscisic Acid Homeostasis in Drought Stress Response - Baek, Dongwon; Shin, Gilok; Kim, Min Chul; Shen, Mingzhe; Lee, Sang Yeol; Yun, Dae-Jin (Frontiers in Plant Science, 2020)
Drought stress, a major environmental factor, significantly affects plant growth and reproduction. Plants have evolved complex molecular mechanisms to tolerate drought stress. In this study, we investigated the function of the Arabidopsis thaliana RPD3-type HISTONE DEACETYLASE 9 (HDA9) in response to drought stress. The loss-of-function mutants hda9-1 and hda9-2 were insensitive to abscisic acid (ABA) and sensitive to drought stress. The ABA content in the hda9-1 mutant was reduced in the WT plant. Most histone deacetylases in animals and plants form complexes with other chromatin-remodeling components, such as transcription factors. In this study, we found that HDA9 interacts with the ABA INSENSITIVE 4 (ABI4) transcription factor using a yeast two-hybrid assay and co-immunoprecipitation. The expression of CYP707A1 and CYP707A2, which encode (+) -ABA 8′-hydroxylases, key enzymes in ABA catabolic pathways, was highly induced in the hda9-1, hda9-2, abi4, and hda9-1 abi4 mutants upon drought stress. Chromatin immunoprecipitation and quantitative PCR showed that the HDA9 and ABI4 complex repressed the expression of CYP707A1 and CYP707A2 by directly binding to their promoters in response to drought stress. Taken together, these data suggest that HDA9 and ABI4 form a repressive complex to regulate the expression of CYP707A1 and CYP707A2 in response to drought stress in Arabidopsis.